(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
The paper proposes a general numerical framework to simplify a CAD model into a volume mesh model under reliable control of certain prescribed physical quantity that the designer is interested in. Different from previous work, the proposed approach does not assume that the candidate features have been detected and can directly generate the simplified volume mesh model. In addition, it can efficiently estimate the quantitative impact of each individual feature via solving a linear equation of small dimension less than 10. This is achieved by reformulating the problem as estimating the solution differences caused by different stiffness matrices, using the combined approximation approach. Performance of this approach is demonstrated via numerical 2D examples.